Atezolizumab/bevacizumab and lenvatinib for hepatocellular carcinoma: A comparative analysis in a European real-world cohort - de Castro, Tiago; Welland, Sabrina; Jochheim, Leonie; Leyh, Cathrine; Shmanko, Kateryna; Finkelmeier, Fabian; Jeliazkova, Petia; Jefremow, Andre; Gonzalez-Carmona, Maria A.; Kandulski, Arne; Roessler, Daniel; Khaled, Najib Ben; et al. (Hepatology Communications, 2024)
Background: Immunotherapy-based combinations are currently the standard of care in the systemic treatment of patients with HCC. Recent studies have reported unexpectedly long survival with lenvatinib (LEN), supporting its use in first-line treatment for HCC. This study aims to compare the real-world effectiveness of LEN to atezolizumab/bevacizumab (AZ/BV). Methods: A retrospective analysis was conducted to evaluate the effectiveness and safety of frontline AZ/BV or LEN therapy in patients with advanced HCC across 18 university hospitals in Europe. Results: The study included 412 patients (AZ/BV: n = 207; LEN: n = 205). Baseline characteristics were comparable between the 2 treatment groups. However, patients treated with AZ/BV had a significantly longer median progression-free survival compared to those receiving LEN. The risk of hepatic decompensation was significantly higher in patients with impaired baseline liver function (albumin-bilirubin [ALBI] grade 2) treated with AZ/BV compared to those with preserved liver function. Patients with alcohol-associated liver disease had poorer baseline liver function compared to other etiologies and exhibited a worse outcome under AZ/BV. Conclusions: In this real-world cohort, survival rates were similar between patients treated with LEN and those treated with AZ/BV, confirming that both are viable first-line options for HCC. The increased risk of hepatic decompensation in patients treated with AZ/BV who have impaired baseline liver function underscores the need for careful monitoring. Future trials should aim to distinguish more clearly between metabolic dysfunction–associated steatotic liver disease and alcohol-associated liver disease.
CRIS-Team Scopus Importer:2024-11-22
Keywords: albumin-bilirubin grade; hepatic dysfunction; immunotherapy; liver cancer; tyrosine kinase inhibitor